Pengembangan Media Kartu Kuartet Berbantuan QR Code untuk Meningkatkan Hasil Belajar - Nadia, Amalia Salma; Andaryani, Eka Titi (Universitas Muhammadiyah Magelang, 2026)
This study seeks to develop learning materials utilizing quartet cards integrated with QR codes and to evaluate their practicality and efficacy in enhancing learning outcomes in Pancasila Education concerning Indonesian Cultural Diversity. The research and development (R&D) methodology employed the ADDIE (analysis, design, development, implementation, and evaluation) framework. The participants were fifth-grade pupils from Jatisari Elementary School. The data gathering encompassed interviews, questionnaires, assessments of learning achievements, and recordkeeping. Data analysis was performed descriptively and inferentially utilizing normality tests, paired sample t-tests, and N-Gain computations. The findings indicated that the QR code-assisted quad card media was considered very viable based on validation by material and media specialists. The paired sample t-test results indicated a significant difference in learning outcomes pre- and post-media usage. The N-Gain computation revealed a moderate enhancement in learning results. Consequently, the QR code-enhanced quad card medium is efficacious in enhancing learning results in Pancasila Education.